Asymmetric winter warming advanced plant phenology to a greater extent than symmetric warming in an alpine meadow. (26th June 2017) - Suonan, Ji; Classen, Aimée T.; Zhang, Zhenhua; He, Jin‐Sheng
Abstract: The warming of terrestrial high‐latitude ecosystems, while increasing, will likely be asymmetric across seasons—where winter non‐growing seasons will warm more than summer‐growing seasons. Asymmetric winter warming in temperature‐sensitive ecosystems may delay spring phenological events by reducing the opportunity that a plants' chilling requirement is met. Similarly, symmetric warming can advance spring phenology. To explore the impact of asymmetric warming on plant phenology, we applied a year‐round warming and a winter warming treatment to our experimental plots. Over a 2‐year period, we monitored leaf‐out and flowering phenology for 11 plant species. There was variation among species, however, both winter and year‐round warming, advanced the leaf‐out day and the first flowering day relative to the control treatment. Winter warming advanced leaf‐out and flowering phenology by 11.1 (±2.4) and 12.6 (±2.9) days respectively. However, year‐round warming had less of an impact advancing leaf‐out and flowering phenology by 5.1 (±2.1) and 10.0 (±3.0) days respectively. Our study provides direct evidence that asymmetric winter warming has a larger impact on plant phenology than symmetric year‐round warming. Increasing soil temperature in the winter from below to above freezing temperatures advanced the spring phenology of alpine plants. Winter warming increased soil temperature more than year‐round warming, which explains why phenology advanced under winter warming more than under year‐round warming. In addition, early or mid‐season flowering plant species displayed different phenology strategies in warmer winters. Relative to other ecosystems, alpine ecosystems such as the Tibetan Plateau will likely respond to asymmetric warming given the higher amplitude of winter temperature increases due to climatic warming. Our data indicate that seasonal variation in warming should be considered when predicting and modelling the response of alpine ecosystems to climatic change. A plain language summary is available for this article. Abstract : Plain Language Summary